The Digestibility of Banana Peel and Testa coconut and Its Effects on the Growth and Mortality of Black Soldier Fly Larvae (Hermetia illucens) at Constant Feeding Rates - Putra, Ramadhani Eka; Margareta, Alfariana; Kinasih, Ida (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
Organic waste produced by economic activities may create health, aesthetic, and economic problems. One of the approaches applied to solve this problem is the utilization of decomposer macrofauna to decompose the waste. One of the decomposers with great potential is Black Soldier Fly larvae (Hermetia illucens) that can consume various types of organic wastes and converts it into biomass with high protein and lipid content. In this study, banana peels and coconut testa had been fed to the larvae at 200 mg/larvae/day as the objects that represented organic wastes with low fiber content and high fiber content respectively. The purpose of this study was to observe the growth and efficiency of BSF larvae in decomposing those wastes. The analysis was conducted on some parameters such as the growth and consumption rate, the efficiency of conversion of digested (ECD), waste reduction index, and mortality rate. The results showed that BSF larvae THAT consumed banana peel had a higher final weight (58.24 mg), growth rate, and consumption rate while the mortality rate was lower than BSF larvae that consumed coconut testa. The ECD of the larvae group that consumed banana peel was higher than the larvae group that consumed coconut testa. The waste reduction index of banana peel was higher than coconut testa (1.5 and 1.4, respectively). The larvae that consumed coconut testa had a longer pupation period (9±1,75 days) compared to the larvae that consumed banana peel. Based on this result, it can be concluded that the fiber content of organic waste affected the decomposition rate and growth of BSF larvae.